الحركة الجمعوية والبناء الديمقراطي في الجزائر المُمكنات والتحديات - غربي, عزوز (Université de M'sila, 2019)
الملخص: تجمع معظم الأدبيات السياسية على الأهمية الكبيرة التي يحتلها المجتمع المدني في شكله الجمعوي، وذلك بالنظر لما يؤديه من ادوار وعلى عديد المستويات سواء منها الاجتماعية والاقتصادية والثقافية...، لذلك فإن التعرف على طبيعة الحركة الجمعوية بالجزائر وبنيتها وخلفيات تشكلها و انبعاثها، والإستراتيجيات المختلفة التي تتبعها في تحقيق أهدافها. وكذا على علاقاتها وتعاملها مع مختلف الأطراف في ظل موازين القوى القائمة، ومكانة كل طرف فيها، مما سيؤدي إلى توضيح مدى مساهمة الحركة الجمعوية وبالفاعلية المطلوب أن تكون في البناء الديمقراطي بالجزائر، أم أنها انحسرت وتراجعت بالنظر للتحديات التي تواجهها، وهو ما ستحاول أن تعالجه هاته الورقة وتجيب عنه. الكلمات المفتاحية: الحركة الجمعوية ، البناء الديمقراطي ، المجال السياسي . Associative movement and the democratic issue in Algeria Possibilities and challenges Abstract: Gathered most of the political literature on the great importance of which is occupied by civil society in the form associative , given what play of roles and on many levels, including the social, economic and cultural ... , therefore, to identify the nature of the associative movement in Algeria , structure and backgrounds formed and emitted , and the different strategies that followed in achieving its objectives . As well as the relations and dealing with the various parties in the light of the balance of power existing , and the status of each party, which will lead to clarify the contribution of the associative movement and efficiency required to be in the democratic construction in Algeria , or is it receded and fell given the challenges they face, to become a void in instead of public space , which will try to be addressed by following the paper and answer it.
Keywords: الحركة الجمعوية ، البناء الديمقراطي ، المجال السياسي